2010
DOI: 10.1179/joc.2010.22.5.328
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bacterial Uptake and Bactericidal Properties of Ofloxacin Loaded on Bioadhesive Hydrogels AgainstPseudomonas aeruginosa

Abstract: Carbomer hydrogels 971pNf, 934pNf and 940Nf loaded with ofloxacin were characterized and their antimicrobial properties evaluated. bactericidal profiles show improved efficacy and prolonged activity exhibited by ofloxacin-containing hydrogels against Pseudomonas aeruginosa. Analysis of bactericidal index (BI) values after a short time of drug exposure confirms the higher potency of hydrogels compared with that of ofloxacin. Increased BI values observed after 24 h indicate prolonged action against the microorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…3C and 4). Accordingly, enhanced bacterial uptake of OFX loaded bioadhesive hydrogels or OFX-containing Eudragit E100 ® dispersions were reported to increase bactericidal properties against P. aeruginosa [29,30]. In the present study, OFX-mPEG-PLGA nanoparticles consistently showed better bactericidal activity against all the tested pathogenic bacterial strains, as revealed by the severe reduction in the number of colonies than the free drug or OFX-PLGA nanoparticles ( Fig.…”
Section: Discussionsupporting
confidence: 61%
“…3C and 4). Accordingly, enhanced bacterial uptake of OFX loaded bioadhesive hydrogels or OFX-containing Eudragit E100 ® dispersions were reported to increase bactericidal properties against P. aeruginosa [29,30]. In the present study, OFX-mPEG-PLGA nanoparticles consistently showed better bactericidal activity against all the tested pathogenic bacterial strains, as revealed by the severe reduction in the number of colonies than the free drug or OFX-PLGA nanoparticles ( Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Strategies to minimize the low OM‐permeability of P. aeruginosa could significantly contribute to the success of therapy for infections with this organism. Several reports describe the effect of cationic peptides as antimicrobial agents or diverse agents as detergents or polymers used in attempts to alter the OM‐permeability of Gram‐negative bacteria (Mugabe et al ., ; Dillen et al ., ; Tin et al ., ; Romero et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…They can act as defensive molecules shaping microbial communities by killing or by inhibiting growth (2,19). However, many recent publications show that the role of specialized metabolites may be more complex, as they can induce biofilm formation and act as signaling molecules (47,48). Therefore, it was not surprising that we identified a transposon insertion mutant in the M. xanthus hsf gene cluster known to regulate specialized metabolite production (38).…”
Section: Discussionmentioning
confidence: 87%